Behavioural compensation for limited grazing time by herded cattle in central Nigeria - Bayer, W. (Elsevier, 1990)
The grazing behaviour in 12 cattle herds (mean size 45 head) mainly of the Banaji (White Fulani) breed kept by Fulani pastoralists was studied by analysing the diurnal pattern of grazing activity during 5 herd-days per month over 1 year. Herding restricted animal access to pasture to only 8.4 h/day as an annual average. The herding period was longest ( 10.5 h) in the transition from dry to wet season and shortest ( 7 h) in the late wet season. The peaks in grazing activity in free-ranging herbivores were not evident in the herded cattle, whose grazing activity remained high throughout the herding day. Resting, including ruminating, accounted for only 5 percent of herding time. Other studies of restricted grazing by African cattle showed a reduction in animal production only if forage was scarce or of low quality. The Fulani herds had access to a variety of grazing resources throughout the year. Any possible limitation in animal production due to restricted grazing time must be seen in the wider context of the land-use system, in which the Fulani herding practices permit an integration of cropping and livestock husbandry.